STRENGTHENING SOCIAL RESILIENCE THROUGH CIVIC ENGAGEMENT IN A MULTICULTURAL SOCIETY: CASE STUDY IN INDONESIA: Received: 16th May 2025, Revised: 18th June 2025, 24th June 2025, Accepted: 1st July 2025, Date of Publication: 15th July 2025 - Puji Nur Ekowati, (PEOPLE: International Journal of Social Sciences, 2025)
Social resilience is a fundamental aspect for multicultural societies, such as Indonesia. The cultural richness of a country is a gift because it has the potential to become a national strength. The diversity of religions, cultures, and customs can contribute to tourism and academics. However, the diversity that exists in a society can be a threat if it is not balanced with an attitude of mutual respect, tolerance, and openness. Social diversity is prone to excessive ethnocentrism, the emergence of identity politics, and social polarization. The massive use of social media in the current digital era increases the risk of social friction that can trigger conflict. Therefore, civic engagement in national life has an important role in fostering an attitude of mutual respect and tolerance. In Indonesia, civic engagement has a wide scope, ranging from deliberation activities at the local level to activities at the national level, such as elections. This study answers the question of how effective civic engagement is in creating social cohesion and strengthening social resilience. The purpose of this study is to examine how civic engagement can increase social resilience in multicultural societies in Indonesia. The method used in this study is qualitative, based on a literature review. This study is expected to provide theoretical contributions in strengthening social resilience through community participation in multicultural countries on a global scale, especially to face challenges in the ever-growing digital era.